Environmental Scan of Return to Work Programs for Trauma-Related Mental Health Conditions. (3rd July 2021) - Edgelow, Megan; Lewis, Megan; Toope, Melanie; Cramm, Heidi
Abstract: Exposure to psychological trauma can cause disruptions in employment; however, program-level return to work (RTW) best practices for clients with trauma-related mental health conditions are limited. We completed an environmental scan to identify RTW programs for this population. English-language webpages from Australia, Canada, New Zealand, the UK, and the USA were included in the scan. Resources were reviewed and informed a SWOT (strength, weakness, opportunity, and threat) analysis. The environmental scan found 35 programs that provide RTW services for this population. Further research, including studies that focus on the efficacy of RTW programs for this population, is required.